Non-tumor cell IDO1 predominantly contributes to enzyme activity and response to CTLA-4/PD-L1 inhibition in mouse glioblastoma - Zhai, Lijie (Brain Behav Immun, 2017)
Glioblastoma (GBM) is the most common malignant brain tumor in adults with a median survival of 14.6 months. A contributing factor to GBM aggressiveness is the intratumoral expression of the potently immunosuppresive enzyme, indoleamine 2,3 dioxygenase 1 (IDO1). The enzymatic activity of IDO1 is associated with the conversion of tryptophan into downstream kynurenine (Kyn), which has previously been hypothesized to contribute toward the suppression of tumor immunity. Utilizing the syngeneic, immunocompetent, intracranial GL261 cell GBM model, we previously demonstrated that tumor cell-, but not non-tumor cell-IDO1, suppresses T cell-mediated brain tumor regression in mice. Paradoxically, we also showed that the survival advantage mediated by immune checkpoint blockade is abrogated by non-tumor cell IDO1-deficiency. Here, we have built on our past observations and confirm the maladaptive role of tumor cell IDO1 in a novel mouse GBM model. We also demonstrate that, non-tumor cells, rather than mouse GBM cells, are the dominant contributor to IDO1-mediated enzyme activity. Finally, we show the novel associations between maximally-effective immune-checkpoint blockade-mediated survival, non-tumor cell IDO1 and intra-GBM Kyn levels. These data suggest for the first time that, GBM cell-mediated immunosuppression is IDO1 enzyme independent, while the survival benefits of immune checkpoint blockade require non-tumor cell IDO1 enzyme activity. Given that current clinical inhibitors vary in their mechanism of action, in terms of targeting IDO1 enzyme activity versus enzyme-independent effects, this work suggests that choosing an appropriate IDO1 pharmacologic will maximize the effectiveness of future immune checkpoint blockade approaches.